Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the equation [tex]\(\log_3 x + \log_3 (x^2 + 2) = 1 + 2 \log_3 x\)[/tex], let's go through the solution step-by-step.
1. Combine the logarithmic terms on the left-hand side:
[tex]\[ \log_3 x + \log_3 (x^2 + 2) = \log_3 \left( x \cdot (x^2 + 2) \right) \][/tex]
Thus, the equation becomes:
[tex]\[ \log_3 \left( x(x^2 + 2) \right) = 1 + 2 \log_3 x \][/tex]
2. Simplify the expression inside the logarithm:
[tex]\[ x(x^2 + 2) = x^3 + 2x \][/tex]
So the equation now is:
[tex]\[ \log_3 (x^3 + 2x) = 1 + 2 \log_3 x \][/tex]
3. Express [tex]\(2 \log_3 x\)[/tex] as a single logarithm:
[tex]\[ 2 \log_3 x = \log_3 x^2 \][/tex]
So the equation can be rewritten as:
[tex]\[ \log_3 (x^3 + 2x) = 1 + \log_3 x^2 \][/tex]
4. Use the property of logarithms to combine [tex]\(1\)[/tex] and [tex]\(\log_3 x^2\)[/tex]:
[tex]\[ 1 + \log_3 x^2 = \log_3 3 + \log_3 x^2 = \log_3 (3x^2) \][/tex]
Hence, the equation becomes:
[tex]\[ \log_3 (x^3 + 2x) = \log_3 (3x^2) \][/tex]
5. Since the logarithmic functions with the same base are equal, their arguments must be equal:
[tex]\[ x^3 + 2x = 3x^2 \][/tex]
6. Solve the algebraic equation:
Rearrange the equation:
[tex]\[ x^3 + 2x - 3x^2 = 0 \][/tex]
Simplifying further:
[tex]\[ x^3 - 3x^2 + 2x = 0 \][/tex]
7. Factor out the common term [tex]\(x\)[/tex]:
[tex]\[ x(x^2 - 3x + 2) = 0 \][/tex]
This gives us:
[tex]\[ x = 0 \quad \text{or} \quad x^2 - 3x + 2 = 0 \][/tex]
8. Solve the quadratic equation:
[tex]\[ x^2 - 3x + 2 = 0 \][/tex]
Factorizing the quadratic equation:
[tex]\[ (x - 1)(x - 2) = 0 \][/tex]
This gives us:
[tex]\[ x = 1 \quad \text{or} \quad x = 2 \][/tex]
So, the solutions to the equation [tex]\(\log_3 x + \log_3 (x^2 + 2) = 1 + 2 \log_3 x\)[/tex] are:
[tex]\[ x = 1 \quad \text{and} \quad x = 2 \][/tex]
Negative values [tex]\(x = -2\)[/tex] and [tex]\(x = -1\)[/tex] are not valid solutions as logarithms of non-positive numbers are undefined in real numbers. Hence, the valid solutions are [tex]\(x = 1\)[/tex] and [tex]\(x = 2\)[/tex].
1. Combine the logarithmic terms on the left-hand side:
[tex]\[ \log_3 x + \log_3 (x^2 + 2) = \log_3 \left( x \cdot (x^2 + 2) \right) \][/tex]
Thus, the equation becomes:
[tex]\[ \log_3 \left( x(x^2 + 2) \right) = 1 + 2 \log_3 x \][/tex]
2. Simplify the expression inside the logarithm:
[tex]\[ x(x^2 + 2) = x^3 + 2x \][/tex]
So the equation now is:
[tex]\[ \log_3 (x^3 + 2x) = 1 + 2 \log_3 x \][/tex]
3. Express [tex]\(2 \log_3 x\)[/tex] as a single logarithm:
[tex]\[ 2 \log_3 x = \log_3 x^2 \][/tex]
So the equation can be rewritten as:
[tex]\[ \log_3 (x^3 + 2x) = 1 + \log_3 x^2 \][/tex]
4. Use the property of logarithms to combine [tex]\(1\)[/tex] and [tex]\(\log_3 x^2\)[/tex]:
[tex]\[ 1 + \log_3 x^2 = \log_3 3 + \log_3 x^2 = \log_3 (3x^2) \][/tex]
Hence, the equation becomes:
[tex]\[ \log_3 (x^3 + 2x) = \log_3 (3x^2) \][/tex]
5. Since the logarithmic functions with the same base are equal, their arguments must be equal:
[tex]\[ x^3 + 2x = 3x^2 \][/tex]
6. Solve the algebraic equation:
Rearrange the equation:
[tex]\[ x^3 + 2x - 3x^2 = 0 \][/tex]
Simplifying further:
[tex]\[ x^3 - 3x^2 + 2x = 0 \][/tex]
7. Factor out the common term [tex]\(x\)[/tex]:
[tex]\[ x(x^2 - 3x + 2) = 0 \][/tex]
This gives us:
[tex]\[ x = 0 \quad \text{or} \quad x^2 - 3x + 2 = 0 \][/tex]
8. Solve the quadratic equation:
[tex]\[ x^2 - 3x + 2 = 0 \][/tex]
Factorizing the quadratic equation:
[tex]\[ (x - 1)(x - 2) = 0 \][/tex]
This gives us:
[tex]\[ x = 1 \quad \text{or} \quad x = 2 \][/tex]
So, the solutions to the equation [tex]\(\log_3 x + \log_3 (x^2 + 2) = 1 + 2 \log_3 x\)[/tex] are:
[tex]\[ x = 1 \quad \text{and} \quad x = 2 \][/tex]
Negative values [tex]\(x = -2\)[/tex] and [tex]\(x = -1\)[/tex] are not valid solutions as logarithms of non-positive numbers are undefined in real numbers. Hence, the valid solutions are [tex]\(x = 1\)[/tex] and [tex]\(x = 2\)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.